Ilmu Sosial dan Kemampuan Berpikir Kritis Matematis - Nurochim .; Siti Ngaisah (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2020)
In scientific studies there should be integration of science. Because with integration, knowledge will be comprehensively understood. Science integration should also be carried out to integrate social science and mathematics. The integration can be methodology integration, characteristic integration, and theoretical integration. The method used in this article is literature review. In this article it is revealed that social science consists of various disciplines related to human life. The disciplines that make up social science are History, Sociology, Anthropology, Economics, and Geography. The science discipline is based on theories developed empirically by figures based on time and space. Social science functions to form people who are aware of their rights and obligations. Therefore it is very important to develop mathematical critical thinking skills before studying social science. So that in studying social science, complete knowledge is obtained.